Did liquidity providers become liquidity seekers? - Jaewon Choi; Or Shachar (Federal Reserve Bank of New York, 2013)
The misalignment between corporate bond and credit default swap (CDS) spreads (i.e., CDSbond basis) during the 2007-09 financial crisis is often attributed to corporate bond dealers shedding off their inventory, right when liquidity was scarce. This paper documents evidence against this widespread perception. In the months following Lehman's collapse, dealers, including proprietary trading desks in investment banks, provided liquidity in response to the large selling by clients. Corporate bond inventory of dealers rose sharply as a result. Although providing liquidity, limits to arbitrage, possibly in the form of limited capital, obstructed the convergence of the basis. We further show that the unwinding of precrisis 'basis trades' by hedge funds is the main driver of the large negative basis. Price drops following Lehman's collapse were concentrated among bonds with available CDS contracts and high activity in basis trades. Overall, our results indicate that hedge funds that serve as alternative liquidity providers at times, not dealers, caused the disruption in the credit market.
Keywords: G12; G01; 330; CDS-bond basis; limits to arbitrage; credit default swaps; liquidity; corporate bonds; Volcker rule